Electrodes for electrochemical devices
The described manufacturing method for dry electrodes addresses wrinkles and mechanical performance issues by using high-temperature low-shear mixing and controlled calendaring, resulting in improved flexibility and adhesion, suitable for mass production with reduced defects.
Patent Information
- Application Number
- JP2024542192
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-20
- Filing Date
- 2023-04-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-20
AI Technical Summary
Conventional dry electrodes face issues such as wrinkles, reduced mechanical performance, and difficulty in mass production due to high shear mixing processes, which lead to non-uniform drying and poor adhesion with the current collector, resulting in defects like pinholes and cracks.
A manufacturing method involving high-temperature low-shear mixing, controlled compression, and calendaring processes to minimize fine powder generation and maximize binder fiber, ensuring a compression ratio of 15% or less, length expansion rate of 4% or less, and gap ratio of 100% to 140%, with optional primer layers to improve adhesion and flatness.
The method produces electrodes with improved flexibility, reduced wrinkles, and enhanced mechanical properties, facilitating mass production by minimizing defects and ensuring uniform adhesion to the current collector.
Smart Images

Figure 2025502329000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to an electrode for an electrochemical element, in particular, a dry electrode and a method for producing the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0049198 filed on April 20, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy sources, and one of the most actively researched areas of this is the field of electrochemical power generation and storage.
[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the fields in which it is used are gradually expanding.
[0005] Lithium secondary batteries, a representative example of such secondary batteries, are not only being used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline and diesel vehicles, which are one of the main causes of air pollution, and their use is expanding to include auxiliary power sources for grid-connected vehicles.
[0006] The manufacturing process of such a lithium secondary battery is roughly divided into three steps: an electrode process, an assembly process, and a chemical formation process. The electrode process is further divided into an active material mixing process, an electrode coating process, a drying process, a rolling process, a slitting process, a winding process, etc.
[0007] Among these, the active material mixing process is a process of mixing coating materials for forming an electrode active layer where an electrochemical reaction actually occurs in the electrode. More specifically, the electrode active material, which is an essential element of the electrode, other additives such as conductive materials and fillers, binders for binding between powder particles and adhesion to the current collector, and solvents for imparting viscosity and dispersing powder, are mixed to produce a fluid slurry.
[0008] The composition mixed to form the electrode active layer is also called an electrode mixture in a broad sense.
[0009] Then, an electrode coating process is performed in which the electrode mixture is coated on an electrically conductive current collector, and a drying process is performed in which the solvent contained in the electrode mixture is removed. The electrode is then rolled to a predetermined thickness.
[0010] Meanwhile, during the drying process, the solvent contained in the electrode mixture evaporates, which may cause defects such as pinholes and cracks in the already formed electrode active layer. In addition, since the inside and outside of the active layer are not dried uniformly, a powder floating phenomenon may occur due to the difference in the evaporation speed of the solvent, i.e., powder in the first dried area floats up and forms a gap with the area that dries later, which may deteriorate the quality of the electrode.
[0011] Unlike conventional electrodes (also called wet electrodes) that are manufactured using a solvent, there has been active research in recent years into the manufacture of electrodes (also called dry electrodes) that are manufactured without using a solvent.
[0012] The dry electrode is generally manufactured by laminating an electrode film, which is manufactured in a film form containing an active material, a binder, etc., on a current collector. In order to fiberize the binder during the process, a high shear mixing process such as jet milling is performed. When the high shear mixing process is applied to a fragile active material, a large amount of fine powder with a small powder size is generated, which tends to reduce mechanical and electrochemical properties, and excessive high shear mixing may cut the generated binder fibers and reduce the flexibility of the electrode film. In addition, during the jet milling process, components adhere to the inside of the equipment, hindering the flow of high-pressure air and clogging the flow path, making mass production difficult.
[0013] In addition, the electrode film manufactured in this way is densified in order to laminate it to the current collector, and high pressure is used to bond it to the current collector during the process. During this process, the area of the current collector where the electrode film is installed (covered area) expands, but the area of the current collector where the electrode film is not installed (uncovered area) does not expand, which causes the problem of wrinkles occurring around the boundary between the covered and uncovered areas.
[0014] Therefore, there is an urgent need to develop a new manufacturing technology for dry electrodes that can solve these problems. Summary of the Invention [Problem to be solved by the invention]
[0015] Therefore, an object of the present invention is to provide an electrode and a manufacturing method thereof in which the degree of wrinkles occurring at the boundary between an area (coated area) where an electrode active material layer is provided on a current collector and an area (uncoated area) where no electrode active material layer is provided is reduced.
[0016] In addition, the present invention provides a method for manufacturing an electrode, which has improved flexibility and mechanical properties by minimizing pulverization of an active material and maximizing fiberization of a binder. [Means for solving the problem]
[0017] In order to solve the above problems, according to one aspect of the present invention, there is provided a method for manufacturing an electrode according to the following embodiment.
[0018] The method for manufacturing an electrode according to a first embodiment of the present invention includes the steps of: (S10) mixing an electrode material including an electrode active material and a binder polymer to obtain a mixture; (S20) kneading the mixture at a high temperature and low shear rate to obtain a mixture mass; (S30) pulverizing the mixture mass under high shear to obtain a mixed powder for an electrode; (S40) calendaring the mixed powder for an electrode to obtain an electrode film; and (S50) laminating the electrode film on at least one surface of a current collector to form an electrode active material layer, wherein the compressibility of the electrode film is 15% or less, and the compressibility of the electrode film is defined by the following formula 1: [Formula 1] Compression rate (%)=[(T B -T A ) / T B ] x 100 In the above formula 1, T A is the thickness of the electrode film (electrode active material layer) after lamination, and T B is the thickness of the electrode film before lamination.
[0019] According to the second embodiment of the present invention, the linear expansion rate of the electrode film in the first embodiment may be 4% or less. The linear expansion rate may be defined by the following Equation 2. [Formula 2] Length expansion rate (%) = [(L A -L B ) / L B ] x 100 In the above formula 2, L A is the length of the electrode film (electrode active material layer) after lamination, and LB is the length of the electrode film before lamination.
[0020] According to the third embodiment of the present invention, in the first or second embodiment, the porosity ratio of the electrode film is 100% to 140%, and the porosity ratio of the electrode film can be defined by the following Equation 3: [Formula 3] Porosity ratio (%)=(P B / P A ) x 100 In the above formula 3, P A is the porosity of the electrode film (electrode active material layer) after lamination, and P B is the porosity of the electrode film before lamination.
[0021] According to a fourth embodiment of the present invention, in any of the first to third embodiments, the porosity of the electrode film before lamination in step (S50) may be 35% or less, and the porosity of the electrode film after lamination may be 30% or less.
[0022] According to a fifth embodiment of the present invention, in any one of the first to fourth embodiments, the calendaring in step (S40) is performed once or twice or more, and includes at least one time of performing the calendaring under a pressure of 100 kg / cm or more.
[0023] According to a sixth embodiment of the present invention, in any of the first to fifth embodiments, the kneading in the step (S20) may be carried out for 1 to 30 minutes at a shear rate in the range of 10 / s to 500 / s.
[0024] According to a seventh embodiment of the present invention, in any one of the first to sixth embodiments, the kneading in the step (S20) may be carried out at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure.
[0025] According to an eighth embodiment of the present invention, in any one of the first to seventh embodiments, the method for manufacturing an electrode further comprises a step of forming a primer layer on at least one surface of the current collector before the lamination in the step (S50).
[0026] According to another aspect of the present invention there is provided an electrode according to the following embodiments.
[0027] An electrode according to a ninth embodiment of the present invention is an electrode comprising a current collector and an electrode active material layer located on at least one surface of the current collector and comprising an electrode active material and a binder polymer, the binder polymer being fibrous to bind the electrode active material, the electrode comprising a ground portion comprising the electrode active material layer and a current collector region facing the electrode active material layer, and an uncoated portion extending from both sides of the current collector region of the ground portion and including a current collector region not facing the electrode active material layer, the electrode active material layer having a porosity of 30% or less, and the uncoated portion having a flat surface.
[0028] According to a tenth embodiment of the present invention, in the ninth embodiment, a primer layer may be further included between the current collector and the electrode active material layer.
[0029] According to still another aspect of the present invention, there is provided an electrochemical device having the following embodiments.
[0030] The electrochemical device according to the eleventh embodiment of the present invention includes a positive electrode, a negative electrode, and a separation layer interposed between the positive electrode and the negative electrode, and at least one of the positive electrode and the negative electrode may be the electrode of the ninth or tenth embodiment.
[0031] According to a twelfth embodiment of the present invention, in the eleventh embodiment, the separation layer may be a separation membrane or a solid electrolyte membrane. Effect of the Invention
[0032] According to one embodiment of the present invention, it is possible to provide an electrode having improved wrinkle characteristics in a region (uncoated portion) where an electrode active material layer is not formed on a current collector, and a manufacturing method thereof. In particular, it is possible to provide an electrode having a flat uncoated portion by improving wrinkle characteristics at a boundary between a coated portion where an electrode active material layer is formed on a current collector and a uncoated portion where an electrode active material layer is not formed, and a manufacturing method thereof.
[0033] According to an embodiment of the present invention, by introducing a high-temperature low-shear kneading process followed by a pulverization process instead of a high-shear mixing process, it is possible to provide a dry electrode in which pulverization of the active material is minimized, fibrous formation of the binder is maximized, and shear cutting of the fibrous binder is minimized.
[0034] Furthermore, since the process does not involve a high-shear jet milling process, but involves kneading with a kneader and pulverization steps, there is no problem of clogging of flow paths due to aggregation of the components, which is advantageous for mass production.
[0035] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0036] [Figure 1] 1 is a schematic diagram of a process for producing a composite film according to one embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of a process for producing a composite film according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram of an electrode lamination process according to one embodiment of the present invention. [Figure 4A] This is a top view photograph of an electrode in which the surface of the uncoated portion is not flat. [Figure 4B] 1 is a side view of an electrode in which the surface of the uncoated portion is not flat. [Diagram 5]5 is a photograph showing the appearance of the electrodes produced in Example 1 and Comparative Examples 1 to 3 in the present specification. FIG. 5 shows the uncoated and coated parts of the electrodes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The present invention will be described in detail below.
[0038] The present invention relates to a method for producing a dry electrode, in which an electrode film is produced by compressing a powder mixture for an electrode, and the electrode is produced by laminating the electrode film with a current collector, and to a dry electrode.
[0039] In the present specification, the term "electrode film" refers to a film manufactured in the form of a free-standing single sheet using an electrode material including an electrode active material and a binder without the intervention of a solvent. In the present specification, the term "free-standing" refers to a film that can maintain a separate form without relying on other members and can be moved or handled by itself. In addition, in the present specification, the electrode film can be referred to as a "dry electrode film" in that it is manufactured without the intervention of a solvent.
[0040] In the present invention, the electrode film may be formed by compressing a mixed powder for an electrode, as described below. For example, the mixed powder may be accumulated by compression to form a layered structure. The mixed powder for an electrode is a powdered electrode material containing an electrode active material and a binder polymer, and may be obtained by pulverizing a mixture lump containing the electrode active material and the binder polymer, as described below.
[0041] In the present invention, the one electrode film may constitute an electrode active material layer. Alternatively, the one electrode film may be a unit electrode film, and a laminate in which a plurality of unit electrode films are laminated may constitute an electrode active material layer. The electrode active material layer of the present invention is not particularly limited thereto, as long as it is formed by compressing an electrode mixed powder into a sheet shape of a predetermined thickness.
[0042] According to one aspect of the present invention, there is provided a method for manufacturing an electrode, comprising: (S10) mixing an electrode material including an electrode active material and a binder polymer to obtain a mixture; (S20) kneading the mixture at high temperature and low shear rate to obtain a mixture mass; (S30) pulverizing the mixture mass under high shear to obtain a mixed powder for an electrode; (S40) calendaring the mixed powder for an electrode to obtain an electrode film; and (S50) laminating the electrode film on at least one surface of a current collector to form an electrode active material layer.
[0043] In the method for producing the electrode, the compression ratio of the electrode film according to the following formula 1 is 15% or less. [Formula 1] Compression rate (%)=[(T B -T A ) / T B ] x 100 In the above formula 1, T A is the thickness of the electrode film (electrode active material layer) after lamination, and T B is the thickness of the electrode film before lamination.
[0044] According to a conventional dry electrode manufacturing process, when pressure is applied to bond the current collector and the electrode film in the lamination step, a problem has been observed in that the shape of the current collector changes due to partial expansion or non-expansion of the current collector.
[0045] Therefore, the inventors of the present invention have found that the problem of deformation of the current collector caused by the compression rate of the electrode film due to lamination in the lamination process in the manufacturing process of a dry electrode can be improved, thereby manufacturing an electrode with a flat uncoated portion on the current collector, and have completed the present invention.
[0046] In addition, the inventors of the present invention have found that in the lamination process in the manufacturing process of a dry electrode, the flatness of the uncoated area can be further improved by not only the compression ratio but also the length change rate of the electrode film before and after lamination.
[0047] Furthermore, it has been found that in the lamination step in the manufacturing process of a dry electrode, the problem of deformation of the current collector can be improved by adjusting the ratio of porosity before and after lamination.
[0048] Furthermore, they found that in the lamination step in the manufacturing process of a dry electrode, the flatness of the uncoated area can be further improved by controlling the porosity of each electrode film before and after lamination.
[0049] In this specification, the "electrode film before lamination" and the "electrode film after lamination" refer to the electrode film to be evaluated for physical properties before and after the lamination process (S50). Thus, the "electrode film before lamination" may refer to the electrode film immediately before lamination, and according to one embodiment of the present invention, may refer to the electrode film obtained in the step (S40). Also, the "electrode film after lamination" may refer to the electrode film immediately after lamination, and according to one embodiment of the present invention, may refer to the electrode active material layer obtained in the step (S50).
[0050] In this specification, the term "ground portion" refers to a region where an electrode active material layer (or electrode film) is formed on at least one surface of a current collector. In other words, the ground portion refers to the electrode active material layer and the current collector region facing the electrode active material layer. In addition, the term "uncoated portion" refers to a region that is not the ground portion, i.e., a region of the current collector where an electrode active material layer is not formed. In other words, the uncoated portion refers to a region of the current collector that extends from both sides of the current collector region of the ground portion and does not face the electrode active material layer.
[0051] In the present invention, as described above, the compression ratio according to the following formula 1 is 15% or less. [Formula 1] Compression rate (%)=[(T B -T A ) / T B ] x 100 In the above formula 1, T A is the thickness of the electrode film (electrode active material layer) after lamination, and T B is the thickness of the electrode film before lamination.
[0052] In this specification, the compressibility of the electrode film may be defined as a ratio of a thickness reduction caused by the electrode film being compressed at the moment of laminating the electrode film to a current collector, and may be defined by Equation 1 above.
[0053] In the present invention, the compression ratio of the electrode film may be 15% or less, for example, 10% or less, 5% or less, or 2% or less. For example, the compression ratio may be 0.1% to 15%, 1% to 12%, 1% to 10%, 1% to 5%, or 1% to 2%. In the present invention, since the electrode film is compressed after the lamination process for manufacturing the electrode, the thickness of the electrode film is reduced from the thickness before lamination. Therefore, the high compression ratio may mean that the degree of compression of the electrode film is high, and thus the pressure applied to the electrode and the current collector is high. This may mean that the area of the current collector where the electrode film is installed, i.e., the coated part, expands to a large extent, which may cause deformation of the uncoated part of the current collector. In addition, the low compression ratio may mean that the degree of compression of the electrode film is low, and thus the pressure applied to the electrode and the current collector is low. In this case, it may mean that the adhesion between the electrode and the current collector is poor. The present invention has the advantage that the degree of deformation of the shape of the current collector is minimized and excellent adhesive strength between the electrode and the current collector is secured by setting the compression ratio according to the above formula 1 in the above range, however, the mechanism of the present invention is not limited thereto.
[0054] Unless otherwise defined herein, the thickness of the electrode film may be measured using a known means for measuring the thickness of each component in the art, such as a thickness gauge, SEM image, etc. In one embodiment of the present invention, the thickness of the electrode film may be measured using a thickness gauge (Mitutoyo, VL-50S-B), but is not limited thereto.
[0055] In one embodiment of the present invention, the length expansion rate of the electrode film before and after lamination according to the following formula 2 may be 4% or less. [Formula 2] Length expansion rate (%) = [(L A -L B ) / L B ] x 100 In the above formula 2, L A is the length of the electrode film after lamination, and L Bis the length of the electrode film before lamination.
[0056] In one embodiment of the present invention, if the compression ratio due to lamination exceeds the above range, the degree of length deformation of the electrode film before and after lamination becomes large, which may cause a change in shape of the current collector. Thus, according to one embodiment of the present invention, the length expansion ratio of the electrode film may be 4% or less, for example, 3% or less, 2% or less, 1.5% or less, 1% or less, 0.5% or less, or 0% (i.e., no length deformation is observed). For example, the length expansion ratio of the electrode film may be 0.1% to 4%, 0.1% to 3%, 0.1% to 2%, 0.1% to 1%, or 0.1% to 0.5%.
[0057] In this specification, unless otherwise defined, the length of the electrode film may refer to the length measured in the machine direction (MD) of the electrode film. The term "machine direction of the electrode film" refers to the traveling direction of the electrode film during the manufacturing process of the electrode film. FIG. 1 is a schematic diagram of a process of manufacturing an electrode film by calendaring a powder mixture for an electrode according to an embodiment of the present invention. Referring to FIG. 1, when the powder mixture for an electrode 120 is input between a plurality of rolls 110, an electrode film 130 is formed along one direction. At this time, the traveling direction of the manufactured electrode film may be defined as the machine direction (MD) of the electrode film.
[0058] The machine direction (MD) of the electrode film coincides with the orientation direction of fibers in the electrode film, and therefore can be confirmed through the orientation direction of fibers in the film to be manufactured. For example, the machine direction of the electrode film can be confirmed through a scanning electron microscope (SEM) image of the electrode film. The orientation direction of fibers confirmed through the SEM image can coincide with the machine direction (MD) of each of the electrode unit films.
[0059] As described above, in the present invention, the electrode active material layer may be formed in the form of a sheet having a predetermined thickness by thermocompression of at least one mixed powder for an electrode, the mixed powder including an electrode active material and a binder polymer. Thus, the electrode active material layer may include a plurality of pores in its structure depending on the properties, tap density, etc. of the mixed powder for an electrode, and thus the electrode active material layer has a porosity within a predetermined range.
[0060] Unless otherwise defined in the present specification, the porosity can be calculated by the following relational equation using the actual density calculated based on the actual density and composition of each component by measuring the apparent density of only the electrode film by subtracting the volume and weight of the current collector from the volume and weight of the electrode. Porosity (%) = {1-(apparent density / actual density)} x 100
[0061] In one embodiment of the present invention, the porosity ratio of the electrode film before and after the lamination is 100% to 140%, and the porosity ratio of the electrode film can be defined by the following Equation 3: [Formula 3] Porosity ratio (%)=(P B / P A ) x 100 In the above formula 3, P A is the porosity of the electrode film (electrode active material layer) after lamination, and P B is the porosity of the electrode film before lamination.
[0062] In one embodiment of the present invention, the porosity ratio of the electrode film before and after lamination according to the above formula 3 may be 100% to 140%, for example, 100% to 130%, 100% to 125%, 100% to 125%, 100% to 120%, 100% to 110%, or 100% to 105%. In one embodiment of the present invention, by adjusting the porosity ratio before and after lamination of the electrode film to satisfy a specific range in the lamination step of the step (S50), excellent effects can be shown in suppressing deformation of the current collector after lamination and ensuring adhesion between the electrode film and the current collector, but the present invention is not limited thereto.
[0063] In one embodiment of the present invention, within the range satisfying the porosity ratio of the electrode film before and after the lamination in step (S50), the porosity of the electrode film before lamination is 35% or less, for example, but not limited to, 15% to 35%, 20% to 35%, 20% to 33%, 30% to 35%, 20% to 30%, 20% to 25%, or 30% to 33%.
[0064] In another embodiment of the present invention, within a range satisfying the porosity ratio of the electrode film before and after the lamination in step (S50), the porosity of the electrode film after lamination in step (S50) is 30% or less, for example, 20% to 30%, 22% to 28%, or 23% to 26%, but is not limited thereto.
[0065] In still another embodiment of the present invention, within a range satisfying the porosity ratio of the electrode film before and after the lamination in step (S50), the porosity of the electrode film before lamination may be 35% or less, and the porosity of the electrode film after lamination may be 30% or less.
[0066] According to one embodiment of the present invention, when the porosity of each electrode film before and after lamination in step (S50) satisfies the above range, it may be preferable in terms of ensuring flatness in the uncoated portion of the electrode and ensuring adhesive strength between the electrode and the current collector, but the present invention is not limited thereto.
[0067] In one embodiment of the present invention, when the porosity of the electrode film before lamination is realized to be low to a target porosity level in the electrode film after lamination, the porosity ratio before and after lamination is formed low, which can have a more advantageous effect in ensuring the flatness of the uncoated area, but the present invention is not limited thereto.
[0068] Hereinafter, a method for manufacturing an electrode in which at least one of the conditions of the compression ratio, the length expansion ratio, and the void ratio before and after lamination is satisfied during the lamination process in step (S50) and wrinkles in the non-coated area are improved will be described in detail for each step.
[0069] First, step (S10) is a step of obtaining a mixture of electrode materials by mixing electrode materials to obtain a mixed powder for an electrode used in manufacturing an electrode film.
[0070] The electrode material includes an electrode active material and a binder polymer.
[0071] The electrode active material may be a positive electrode active material or a negative electrode active material depending on the polarity of the electrode to be manufactured.
[0072] In one embodiment of the present invention, when the electrode is used as a positive electrode, the electrode active material may be a positive electrode active material. The positive electrode active material may include, but is not limited to, a lithium transition metal oxide, a lithium metal iron phosphate, a lithium nickel-manganese-cobalt oxide, an oxide in which a part of the lithium nickel-manganese-cobalt oxide is substituted with another transition metal, or two or more of these. Specifically, the positive electrode active material may be, for example, a lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ) and compounds substituted with one or more transition metals, and compounds of the formula Li 1+x Mn 2-x O 4 (where x is 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxides such as Lithium copper oxide (Li 2 CuO 2 ) and LiV 3 O 8 , LiV 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-x M x O 2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3) and Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-x M x O 2 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li 2 Mn 3 MO 8 (wherein M=Fe, Co, Ni, Cu, or Zn) and lithium metal phosphate LiMPO 4(Here, M is M = Fe, Co, Ni, or Mn), and lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O 2 (where x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, a + b + c = 1), and an oxide in which part of lithium nickel-manganese-cobalt oxide is substituted with aluminum, Li a [Ni b Co c Mn d Al e ) 1-f M1 f O 2 (M1 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, 0 ≤ f ≤ 0.1), and an oxide in which part of lithium nickel-manganese-cobalt oxide is substituted with other transition metals, Li 1+x (Ni a Co b Mn c M d ) 1-x O 2 (x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, d = 0.001 to 0.03, a + b + c + d = 1, M is any one selected from the group consisting of Fe, V, Cr, Ti, W, Ta, Mg, and Mo), a disulfide compound, and Fe 2 (MoO 4 ) 3 etc. are mentioned, but are not limited thereto.
[0073] In another embodiment of the present invention, when the electrode is used as a negative electrode, the electrode active material can be a negative electrode active material. The negative electrode active material is, for example, carbon such as graphitizable carbon and graphite-based carbon, and Li x Fe 2 O 3 (0 ≤ x ≤ 1), Lix WO 2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8), etc. metal composite oxides, lithium metal, lithium alloy, silicon-based alloy, tin-based alloy, SiO, SiO / C, SiO 2 etc. silicon-based oxides, SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , and Bi 2 O 5 etc. metal oxides, conductive polymers such as polyacetylene, Li-Co-Ni-based materials, etc. can be used, but are not limited thereto.
[0074] In one embodiment of the present invention, the electrode active material is a positive electrode active material, and the positive electrode active material is an oxide Li 1+a [Ni b Co c Mn d Al e 1-a O 2 (0 ≦ a ≦ 0.03, 0.3 ≦ b ≦ 0.95, 0 < c < 0.5, 0 < d < 0.5, 0.001 ≦ e ≦ 0.05, b + c + d + e = 1) may be.
[0075] In other embodiments of the invention, the positive electrode active material can be lithium manganese oxide, lithium metal iron phosphate, lithium nickel-manganese-cobalt oxide, or a mixture of two or more thereof.
[0076] In one embodiment of the present invention, the binder polymer is not particularly limited as long as it can be fibrillated in the manufacturing method described below, particularly in the process of manufacturing the mixture mass. The fibrillation refers to a process of finely dividing a polymer, and can be carried out, for example, by using mechanical shear force. The surface of the polymer fiber fibrillated in this way is loosened, and a large number of fine fibers (fibrils) are generated.
[0077] Non-limiting examples of such binder polymers include polytetrafluoroethylene (PTFE), polyolefin, or a mixture thereof, and more specifically, polytetrafluoroethylene (PTFE). Specifically, the polytetrafluoroethylene (PTFE) may be included in an amount of 60% by weight or more based on the total weight of all binder polymers. Meanwhile, at this time, it goes without saying that the binder material may further include one or more of PEO (polyethylene oxide), PVdF (polyvinylidene fluoride), PVdF-HFP (polyvinylidene fluoride-cohexafluoropropylene), and polyolefin-based polymers.
[0078] In an embodiment of the present invention, the electrode active material layer may further include a conductive material. In an embodiment of the present invention, the conductive material may be included in the electrode mixed powder and introduced into the electrode active material layer.
[0079] The conductive material is not particularly limited as long as it is conductive without causing a chemical change in the battery. For example, graphite such as natural graphite or artificial graphite, carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fiber and metal fiber, metal powder such as carbon fluoride, aluminum, and nickel powder, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive materials such as polyphenylene derivatives can be used. More specifically, in order to uniformly mix the conductive material and improve the conductivity, the conductive material may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, may include carbon black.
[0080] In one embodiment of the present invention, the content of the electrode active material relative to the total weight of the electrode material mixture may be, for example, 80% by weight or more, 90% by weight or more, or 85% to 98% by weight, more specifically, 90% to 98% by weight, or 95% to 98% by weight.
[0081] In one embodiment of the present invention, the content of the binder polymer relative to the total weight of the electrode material mixture may be, for example, 0.5% to 20% by weight, 0.5% to 10% by weight, or 2% to 15% by weight, more specifically, 2% to 10% by weight, or 2% to 5% by weight.
[0082] In one embodiment of the present invention, as described above, the electrode material mixture further includes a conductive material, and the content of the conductive material relative to the total weight of the electrode material mixture may be, for example, 0.1 wt % to 20 wt %, 0.5 wt % to 10 wt %, or 0.5 wt % to 5 wt %, more specifically, 0.5 wt % to 3 wt %, or 1 wt % to 3 wt %.
[0083] In the present invention, the electrode active material layer is derived from an electrode film formed by compressing an electrode mixed powder formed from the mixture of the above-mentioned electrode materials, and the content ratio of the electrode materials may be within the same range as that of the electrode active material layer.
[0084] In the step (S10), the electrode material is mixed so as to uniformly distribute the electrode active material, the binder polymer, and, if necessary, the conductive material, and since these components are mixed in a powder form, the method is not particularly limited as long as it allows simple mixing of these components, and they can be mixed by various methods. However, since the above method is aimed at producing a dry electrode without using a solvent, the above mixing can be performed by dry mixing, and can be performed by putting the above materials into a device such as a blender or a super mixer.
[0085] In one embodiment of the present invention, when the mixing is performed in a blender, the mixture may be prepared by mixing in a blender at 5,000 rpm to 20,000 rpm for 30 seconds to 20 minutes, more specifically, at 10,000 rpm to 15,000 rpm for 30 seconds to 5 minutes to ensure uniformity.
[0086] In another embodiment of the present invention, when the mixing is performed in a super mixer, the mixing may be performed in the super mixer at 500 rpm to 2,500 rpm, specifically 1,000 rpm to 2,000 rpm, to ensure uniformity, and the process time may be adjusted accordingly.
[0087] Next, the step (S20) of kneading the mixture of electrode materials at a high temperature and low shear rate to obtain a mixture mass is carried out.
[0088] The step (S20) is a step for fiberizing the binder from the mixture prepared as above, and is also called a kneading step.
[0089] In one embodiment of the present invention, the binder may be fiberized and the active material may be pulverized, and low shear kneading may be performed to eliminate the problem of the formed fibers being broken, but the step (S20) is not limited thereto.
[0090] At this time, the kneading can be carried out by using, but is not limited to, a kneading machine such as a kneader.
[0091] This kneading is a step in which the binder becomes fibrous and bonds or connects the active material or the active material and the conductive powder, thereby forming a mixture mass with a solid content of 100%.
[0092] In one embodiment of the present invention, the kneading in step (S20) can be carried out at a speed of 10 rpm to 100 rpm for 1 minute to 30 minutes, and more particularly, at a speed of 20 rpm to 50 rpm for 3 minutes to 10 minutes.
[0093] In one embodiment of the present invention, the kneading in step (S20) can be performed at a shear rate in the range of 10 / s to 500 / s for 1 to 30 minutes. More specifically, the shear rate can be in the range of 30 / s to 100 / s. Moreover, such a kneading step can be performed under high temperature and pressure conditions equal to or higher than atmospheric pressure, more specifically, under pressure conditions higher than atmospheric pressure.
[0094] In one embodiment of the present invention, in step (S20), the kneading can be carried out at a temperature in the range of 70° C. to 200° C., more specifically, in the range of 90° C. to 180° C. or 90° C. to 150° C. If the kneading is carried out in the above-mentioned temperature range, it may be preferable in terms of the fiberization of the binder, the agglomeration by the kneading, the ease of film formation during the subsequent calendar processing, and the mechanical properties of the fiberized binder, but the present invention is not limited thereto.
[0095] In one embodiment of the present invention, in step (S20), the kneading can be carried out at atmospheric pressure or higher, specifically, at a pressure of 1 atm to 60 atm, or 1 atm to 30 atm, or 1 atm to 10 atm, or 1.1 atm to 10 atm, or 1.1 atm to 6 atm, or 1.1 atm to 3 atm. When the kneading is carried out in the above pressure range, it may be preferable in terms of the fiberization of the binder and the mechanical properties of the fiberized binder, but the present invention is not limited thereto.
[0096] Thus, in one embodiment of the present invention, the kneading may preferably be performed by a low shear mixing step under high temperature and pressure conditions equal to or higher than atmospheric pressure, instead of high shear mixing.
[0097] The step (S30) is a step of pulverizing the result of the step (S20), specifically the mixture lump obtained by kneading, to obtain a mixed powder for an electrode. In order to immediately process the result of the step (S20), specifically the mixture lump, into a film, a process under strong pressure and high temperature is required. This may cause problems such as the density of the film being excessively high or the film not being uniform. Therefore, after the mixture lump is pulverized to obtain the powder for an electrode, the obtained powder is calendered.
[0098] In one embodiment of the present invention, the grinding can be performed by, but is not limited to, a blender or by an apparatus such as a grinder, such as a cutter mill or a fine impact mill.
[0099] In one embodiment of the present invention, when the grinding is carried out using a blender, the grinding can be carried out specifically at a speed of 500 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically at a speed of 1,000 rpm to 10,000 rpm for 30 seconds to 1 minute.
[0100] In another embodiment of the present invention, when the above-mentioned pulverization is carried out using a cutter mill, the above-mentioned pulverization can be specifically carried out at a speed of 500 rpm or less, for example, 400 rpm to 500 rpm, for 10 seconds to 60 seconds.
[0101] In yet another embodiment of the present invention, when the grinding is carried out using an impact mill, the grinding can be carried out specifically at a speed of 3,000 rpm to 8,000 rpm, for example 4,000 rpm to 7,000 rpm, for 10 seconds to 60 seconds.
[0102] In one embodiment of the present invention, carrying out the above-mentioned pulverization under the above-mentioned conditions may be preferable in terms of powder size and suppressing the generation of fine powder, but the present invention is not limited thereto.
[0103] In one embodiment of the present invention, after the step (S30) and before the calendering step (S40), the method may further include a step of classifying the pulverized mixed powder for an electrode (S31). In the step of classifying, the pulverized mixed powder for an electrode may be obtained by filtering the mixed powder for an electrode having a certain size or more using a mesh having pores of a certain size or less.
[0104] Next, in step (S40), an electrode film is obtained by a method of pressure-bonding and molding the mixed powder for electrodes. In the present specification, the process of pressure-bonding the mixed powder for electrodes to produce a sheet-shaped electrode film is described as a calendaring process. By the calendaring process, the electrode film can be provided in the shape of a sheet having a predetermined thickness. For example, the electrode film obtained through step (S40) may have a shape of a strip whose aspect ratio exceeds 1. In one embodiment of the present invention, the electrode film obtained through step (S40) may have a thickness of 50 μm to 300 μm. More specifically, the electrode film may have a thickness of 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 100 μm, 60 μm to 90 μm, 70 μm to 85 μm, 70 μm to 80 μm, 70 μm to 75 μm, or 80 μm to 85 μm.
[0105] In one embodiment of the present invention, when the electrode active material contained in the electrode film is an oxide in which part of lithium nickel-manganese-cobalt oxide is substituted with aluminum as a positive electrode active material, Li 1+a [Ni b Co c Mn d Al e 1-a O 2 (0 ≦ a ≦ 0.03, 0.3 ≦ b ≦ 0.95, 0 < c < 0.5, 0 < d < 0.5, 0.001 ≦ e ≦ 0.05, b + c + d + e = 1), the electrode film may have a thickness of, for example, 70 μm to 85 μm, 70 μm to 80 μm, or 70 μm to 75 μm, but is not limited thereto.
[0106] In another embodiment of the present invention, when the electrode active material contained in the electrode film contains lithium iron phosphate (LFP) as a positive electrode active material, the electrode film may have a thickness of, for example, 110 μm to 120 μm, but is not limited thereto.
[0107] For example, the calendering process can be performed by a calendering method in which the electrode powder mixture is supplied to a calendering device and thermally compressed using (a plurality of) roll presses included in the calendering device. Also, the calendering process can be performed by a roll-to-roll continuous process.
[0108] In one embodiment of the present invention, the calendering device may include a roll press unit in which two rollers are arranged opposite to each other, and the mixed powder for an electrode may be compressed into a sheet shape by passing through the roll press unit. In one embodiment of the present invention, a plurality of the roll press units are arranged in succession, and the electrode film may be compressed a plurality of times. The number of the roll press units may be appropriately adjusted in consideration of the thickness and rolling ratio of the electrode film.
[0109] 1 is a schematic diagram showing the calendering process 100 according to an embodiment of the present invention. Referring to this, an electrode powder mixture 120 is compressed multiple times using a calendering device having a roll press unit in which two calendering rollers 110 are arranged facing each other, to manufacture an electrode film 130. As described above, the electrode film is manufactured without using a solvent, and therefore can be called a dry electrode film.
[0110] 2 is a schematic diagram showing the calendering process 100 according to another embodiment of the present invention. Referring to this, a calendering device having a roll press unit in which two calendering rollers 110 are arranged facing each other and spaced apart at a predetermined interval is used to pressurize the electrode mixture powder 120 multiple times to manufacture an electrode mixture film 130.
[0111] Meanwhile, the rotational speed ratio of the two rollers in each of the roll press units can be appropriately controlled independently within a range of 1:1 to 1:10. For example, the rotational speed ratio of the two rollers in any one or more of the roll press units can be controlled at a ratio of 1:1 to 1:3. In addition, the temperature of the rollers in each of the roll press units can be independently controlled within a range of 50° C. to 250° C. An electrode film can be manufactured by such a calendering process.
[0112] In one embodiment of the present invention, the narrower the gap between the two rollers of the roll press unit, the higher the compression pressure, and therefore the lower the porosity of the electrode film produced by calendaring. Therefore, the calendar pressure can be adjusted by adjusting the gap between the two rollers or the size of the rollers according to the porosity and thickness of the target electrode film.
[0113] In one embodiment of the present invention, the calendering in step (S40) can be performed once by a single roll press unit, or can be performed two or more times by a plurality of roll press units.
[0114] In one embodiment of the present invention, the calendering in step (S40) may include at least one cycle of pressure, for example, 100 kg / cm or more. Preferably, when the electrode powder mixture is pressed multiple times during the calendering step in step (S40), the pressure can be gradually reduced by repeating the pressurization. In this case, it may be preferable for the pressure during the final pressurization, i.e., the lowest pressure during the calendering step, to be 100 kg / cm or more for the production of the intended electrode film, but the present invention is not limited thereto.
[0115] In one embodiment of the present invention, the electrode active material used in the preparation of the electrode film may include, for example, lithium nickel manganese cobalt aluminum. The lower limit of the calender pressure exemplified above may vary depending on the type of electrode active material used in the preparation of the electrode film, but the present invention is not limited thereto.
[0116] Therefore, the porosity of the electrode film produced by the calendaring process (i.e., the electrode film before lamination) may be 35% or less. Specifically, the porosity of the electrode film obtained through step (S40) may be 35% or less, 30% or less, more specifically, 10% to 35%, 15% to 30%, 20% to 30%, 23% to 26%, or 22% to 24%.
[0117] In one embodiment of the present invention, the calendering in step (S40) may include at least one cycle of calendering under a pressure of, for example, 100 kg / cm or more. Preferably, as described above, when the calendering is performed multiple times in the calendering process, the final calendering may be performed under a pressure of 100 kg / cm or more, but the present invention is not limited thereto.
[0118] In one embodiment of the present invention, the calendering in step (S40) can be performed at a pressure of 500 kg / cm or less within the above-mentioned pressure range, but is not limited thereto.
[0119] In one embodiment of the present invention, the calendering in step (S40) can be performed at a pressure of, for example, 100 kg / cm to 500 kg / cm, for example, 200 kg / cm to 300 kg / cm, or 300 kg / cm to 500 kg / cm, specifically 400 kg / cm to 500 kg / cm, 400 kg / cm to 450 kg / cm, or 415 kg / cm to 450 kg / cm, in order to reduce the porosity of the electrode film obtained by the calendering and reduce the compression rate in the lamination step.
[0120] In one embodiment of the present invention, the electrode film manufactured by the calendaring process as described above may have a crystallinity of the binder polymer in the electrode film controlled to 10% or less or less than 10%. More specifically, the crystallinity of the binder polymer in the electrode film manufactured by the calendaring process may be 5% or less, specifically 1% or less, or 0%. When the crystallinity of the binder polymer in the electrode film is controlled to 10% or less, the flexibility of the electrode film is increased, and there is an advantage that the electrode film is not broken or cracked when it is wound up and stored or unwound. In addition, the increased flexibility can improve mechanical strength, such as improving tensile strength and tensile elongation, but the present invention is not limited thereto.
[0121] In the present specification, the crystallinity (Xc) of the binder polymer can be measured by a differential scanning calorimetry (DSC) and is based on the temperature (peak temperature) at the point where the highest enthalpy is shown during crystallization. Specifically, the crystallinity is expressed as a percentage by dividing the melting enthalpy (ΔHm) value actually measured by DSC by the melting enthalpy (ΔHm°) (equilibrium heat of fusion) value of a theoretical perfect crystal (crystallinity 100%), and can be calculated by the following Equation 4. Here, the melting enthalpy value of a theoretical perfect crystal can be found and used in the Polymer Handbook for known polymers, and can be calculated by an extrapolation method in which the crystallinity is determined by extending two or more points. [Formula 4] Xc(%)=(ΔHm÷ΔHm゜)×100
[0122] According to one embodiment of the present invention, as described above, the porosity of the electrode film manufactured by the calendaring process in this manner may be 35% or less.
[0123] Next, (S50) the electrode film produced as described above is laminated on one or both sides of a current collector to form an electrode active material layer, and then the current collector and the electrode film are joined to produce an electrode.
[0124] In one embodiment of the present invention, the current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and examples of the current collector include stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. In addition, the current collector can improve the adhesive force of the positive electrode active material by forming fine irregularities on its surface, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0125] In one embodiment of the present invention, the thickness of the current collector may be selected as necessary and is not particularly limited, and may be, for example, 5 μm to 50 μm, specifically 10 μm to 30 μm, or 15 μm to 20 μm.
[0126] In one embodiment of the present invention, the current collector may be entirely or partially coated with a conductive primer for reducing surface resistance and improving adhesion. Here, the conductive primer may include a conductive material and a binder, and the conductive material may be, for example, a carbon-based material, as long as it is a material having conductivity. The binder may include a fluorine-based binder (including PVDF and PVDF copolymers) that is soluble in a solvent, an acrylic binder, and a water-based binder.
[0127] For this purpose, in one embodiment of the present invention, the method may further include a step of forming a primer layer on at least one surface of the current collector before the lamination in step (S50).
[0128] In one embodiment of the present invention, the lamination may be a step of rolling and attaching the electrode film to a predetermined thickness on at least one surface of the current collector or on at least one surface of the current collector having a primer layer on the at least one surface. The lamination may also be performed by a lamination roll, and in this case, the lamination roll may be maintained at a temperature of room temperature (25° C.) to 200° C., but is not limited thereto.
[0129] 3 is a schematic diagram showing a lamination process (200) according to an embodiment of the present invention. Referring to this figure, an electrode film 230 is bonded to a current collector 220 to manufacture an electrode 240, and the lamination process is performed by applying pressure with a lamination roller 210. Meanwhile, in the present invention, the electrode film attached to the current collector by lamination as described above is also referred to as an electrode active material layer.
[0130] According to the above-described manufacturing method, an electrode is manufactured in which the compression rate of the electrode film due to lamination is 15% or less.
[0131] In one embodiment of the invention, the compressibility of the electrode film by lamination may be 1% to 15%, 1% to 12%, 1% to 10%, or 1% to 5%.
[0132] In one embodiment of the present invention, an electrode having the above-mentioned compressibility of the electrode film can be manufactured to have a flat surface in the non-coated portion.
[0133] According to another aspect of the present invention, there is provided an electrode comprising a current collector and an electrode active material layer located on at least one surface of the current collector and comprising an electrode active material and a binder polymer, wherein the binder polymer is fibrous to bind the electrode active material, the electrode comprising a grounded portion comprising the electrode active material layer and a current collector region facing the electrode active material layer, and an uncoated portion extending from both sides of the current collector region of the grounded portion and including a current collector region not facing the electrode active material layer, wherein the porosity of the electrode active material layer is 30% or less, and the surface of the uncoated portion is flat.
[0134] In one embodiment of the present invention, the porosity of the electrode active material layer may be specifically 30% or less, 5% to 30%, 10% to 30%, 15% to 30%, 20% to 30%, 20% to 25%, 25% to 30%, or 23% to 26%.
[0135] In one embodiment of the present invention, a primer layer may be further included between the current collector and the electrode active material layer, but the present invention is not limited thereto.
[0136] The current collector, the coated portion, the uncoated portion, the electrode active material layer, the mixed powder for the electrode, the primer layer, and the porosity are the same as those described in the electrode manufacturing method.
[0137] In one embodiment of the present invention, the flatness of the surface of the uncoated portion not having the electrode active material layer on at least one side of the current collector can be confirmed, for example, by visually observing the appearance of the electrode and measuring the maximum height of the uneven shape on the surface of the uncoated portion or the coated portion.
[0138] For example, in one embodiment of the present invention, when the appearance of the electrode is visually observed, if no wrinkles are found in the uncoated portion, it can be said that the surface of the uncoated portion is flat.
[0139] In one embodiment of the present invention, the term "flat surface of the uncoated portion" may refer to a shape in which there is no visually observable curvature on the surface of a region of the current collector on which an electrode active material layer is not formed, or a shape in which the height of the curvature on the surface of the uncoated portion and / or the coated portion is 2 mm or less.
[0140] Fig. 4A shows a photograph of an electrode in which visually visible bends are formed on the surfaces of the uncoated and coated areas. Referring to Fig. 4A, it can be seen that when the uncoated area of an electrode is not flat, wrinkles are formed in the coated area as well.
[0141] FIG. 4B shows a photograph of the bend of the electrode shown in FIG. 4A observed from the side. Referring to FIG. 4B, an electrode having an uneven surface in the uncoated portion can be defined as an electrode in which the maximum height of the bend exceeds 2 mm.
[0142] Therefore, according to an embodiment of the present invention, an electrode having a maximum bending height of 2 mm or less can be defined as an electrode having a flat surface in the uncoated portion.
[0143] In one embodiment of the present invention, when the compression ratio of the electrode film according to the above formula 1 is 15% or less, it can be said that the surface of the non-coated portion is flat.
[0144] In one embodiment of the present invention, when the linear expansion rate of the electrode film according to the above formula 2 is 4% or less, it can be said that the surface of the non-coated portion is flat.
[0145] In one embodiment of the present invention, when the porosity ratio of the electrode film according to the above formula 3 is 100% to 140%, it can be said that the surface of the non-coated portion is flat.
[0146] As described above, in the electrode according to another aspect of the present invention, since the wrinkles in the uncoated portion are flattened, problems such as meandering, in which the electrode is biased to one side during the electrode assembly process, and winding defects can be improved. Therefore, since the electrode can be manufactured without a separate process for flattening the wrinkles in the uncoated portion, there are advantages in that the occurrence rate of electrode defects is significantly reduced and the manufacturing process of the electrode and battery is simplified.
[0147] According to yet another aspect of the present invention, there is provided an electrochemical element comprising a positive electrode, a negative electrode, and a separation layer interposed between the positive electrode and the negative electrode, and using at least one of the positive electrode and the negative electrode as the above-mentioned electrode.
[0148] In one embodiment of the present invention, the separation layer may be a separation membrane or a solid electrolyte membrane.
[0149] The electrochemical device includes any device that performs an electrochemical reaction, and specific examples thereof include all kinds of primary and secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitors, etc. In particular, among the secondary batteries, lithium secondary batteries including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries are preferred.
[0150] The specific structure of the electrochemical element is well known, and therefore will not be described in this specification.
[0151] The electrochemical device according to the present invention may be included as a unit cell in an energy storage device, but the application of the present invention is not limited thereto.
[0152] The specific structure of the energy storage device is well known, and therefore will not be described in this specification.
[0153] The present invention will be described in more detail below with reference to examples. However, the following examples are for illustrating the present invention, and the scope of the present invention is not limited to these examples.
[0154] [Electrode manufacturing] Example 1 Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.87 Co 0.05 Mn 0.07 Al 0.01 ]O 2 96 wt% of ethylenediaminetetraacetate (EPO), 1 wt% of carbon black as a conductive material, and 3 wt% of polytetrafluoroethylene (PTFE) as a binder polymer were put into a blender and mixed at 10,000 rpm for 1 minute to produce a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, which was then operated at a speed of 50 rpm for 5 minutes under a pressure of 1.1 atm to obtain a mixture mass. The mixture mass was put into the blender, pulverized at 10,000 rpm for 40 seconds, and classified using a sieve with 1 mm openings to obtain a mixed powder for electrodes.
[0155] The mixed powder for the electrode was then put into a lap calendar (roll diameter: 200 mm, roll temperature: 100°C, 20 rpm) and the calendaring process was repeated until the porosity was 35% or less. At this time, the pressure between the rolls in the final calendaring process was set to 221 kg / cm to produce an electrode film. The electrode film thus produced had a thickness of 82 μm, a porosity (%) of 31%, and a load of 5.11 mAh / cm. 2 It was.
[0156] A primer layer was formed on a current collector by applying a slurry for forming a primer layer to an aluminum foil and drying it. The primer layer contained carbon black and a PVDF binder in a weight ratio of 1:2. In addition, a lamination process was performed using a roll press maintained at room temperature to laminate the two electrode films prepared above on both sides of the aluminum foil (average thickness: 19 μm) on which the primer layer was formed, so that the porosity of the electrode active material layer was 30% or less, and the electrode film was placed on the current collector to manufacture an electrode in which an electrode active material layer was formed on both sides of the current collector. At this time, the thickness of the electrode film placed on the current collector, i.e., the electrode active material layer, was 75 μm, the porosity (%) was 25.9%, and the load amount was 5.05 mAh / cm. 2 It was.
[0157] Example 2 An electrode film was produced in the same manner as in Example 1, except that the pressure between the rolls during the final calendaring was 264 kg / cm. The electrode film produced after calendaring had a thickness of 81 μm, a porosity (%) of 30.1%, and a load of 5.11 mAh / cm. 2 It was.
[0158] Next, an electrode was manufactured by laminating in the same manner as in Example 1. At this time, the thickness of the electrode film placed on the current collector, i.e., the electrode active material layer, was 72 μm, the porosity (%) was 23.1%, and the load amount was 5.0 mAh / cm 2It was.
[0159] Example 3 An electrode film was produced in the same manner as in Example 1, except that the pressure between the rolls during the final calendaring was 415 kg / cm. The electrode film produced after calendaring had a thickness of 74 μm, a porosity (%) of 23.5%, and a load of 5.11 mAh / cm. 2 It was.
[0160] Next, an electrode was manufactured by laminating in the same manner as in Example 1. At this time, the thickness of the electrode film placed on the current collector, i.e., the electrode active material layer, was 72 μm, the porosity (%) was 23.0%, and the load amount was 5.07 mAh / cm 2 It was.
[0161] Comparative Example 1 The electrode film was produced by carrying out the calendering process in the same manner as in Example 1, except that the pressure between the rolls in the final calendering process was set to 115 kg / cm so that the porosity during the calendering process exceeded 35%. At this time, the thickness of the electrode film immediately after the calendering process and before lamination was 92 μm, the porosity (%) was 37.2%, and the load was 5.21 mAh / cm. 2 It was.
[0162] Thereafter, lamination was performed in the same manner as in Example 1 so as to have the same thickness and porosity as the electrode produced in Example 1, to produce an electrode in which an electrode active material layer was formed on both sides of the current collector. At this time, the thickness of the electrode film (electrode active material layer) placed on the current collector was 74 μm, the porosity (%) was 26.0%, and the load amount was 4.96 mAh / cm. 2 It was.
[0163] Comparative Example 2 By using the same method as in Example 1 and setting the pressure between the rolls in the final calendaring process to 210 kg / cm, the thickness of the electrode film was 83 μm, the porosity (%) was 31.2%, and the load was 5.15 mAh / cm. 2 An electrode film having the following structure was manufactured.
[0164] Thereafter, an electrode was manufactured by laminating in the same manner as in Example 1. At this time, by adjusting the lamination pressure, the thickness of the electrode film (electrode active material layer) placed on the current collector was 68 μm, the porosity (%) was 19.2%, and the load was 4.93 mAh / cm 2 An electrode having the following formula was manufactured.
[0165] Comparative Example 3 The electrode film was produced by carrying out the calendering process in the same manner as in Example 1, except that the pressure between the rolls in the final calendering process was set to 85 kg / cm so that the porosity during the calendering process exceeded 35%. At this time, the thickness of the electrode film immediately after the calendering process and before lamination was 95 μm, the porosity (%) was 39.8%, and the load was 5.16 mAh / cm. 2 It was.
[0166] Thereafter, lamination was performed in the same manner as in Example 1 so that the thickness and porosity were similar to those of the electrode produced in Example 1, and an electrode was produced by lamination. At this time, the thickness of the electrode film (electrode active material layer) placed on the current collector was 76 μm, the porosity (%) was 29.0%, and the load amount was 4.87 mAh / cm 2 It was.
[0167] [Physical property evaluation] Thickness measurement The thickness of the electrode film was measured using a thickness gauge (Mitutoyo, VL-50S-B).
[0168] Compression ratio evaluation The compressibility of the electrode film was evaluated according to the following formula 1. [Formula 1] Compression rate (%)=[(T B -T A ) / T B ] x 100 In the above formula 1, T A is the thickness of the electrode film (electrode active material layer) after lamination, and T B is the thickness of the electrode film before lamination.
[0169] Evaluation of length expansion rate The linear expansion rate of the electrode film of the manufactured electrode was evaluated according to the following Equation 2. [Formula 2] Length expansion rate (%) = [(L A -L B ) / L B ] x 100 In the above formula 2, L A is the length of the electrode film (electrode active material layer) after lamination, and L B is the length of the electrode film before lamination.
[0170] Porosity measurement The volume and weight of the current collector were subtracted from the volume and weight of the manufactured electrode to measure the apparent density of the electrode film alone, and the porosity of the electrode film before and after lamination was measured according to the following equation using the actual density calculated based on the actual density and composition of each component.
[0171] Evaluation of void ratio The porosity ratio of the produced electrode was evaluated according to the following formula 3. [Formula 3] Porosity ratio (%)=P B / P A ×100 In the above formula 3, P A is the porosity of the electrode film (electrode active material layer) after lamination, and P B is the porosity of the electrode film before lamination.
[0172] Evaluation of wrinkles in plain areas The appearance of the produced electrodes was visually observed to evaluate wrinkles in the uncoated areas, that is, the flatness of the uncoated areas.
[0173] At this time, if wrinkles were clearly observed on the plain area, the wrinkle characteristics of the plain area were evaluated as "poor," and if no wrinkles were observed by visual observation, the wrinkle characteristics of the plain area were evaluated as "good."
[0174] FIG. 5 shows photographs of the appearance of the electrodes of Example 1 and Comparative Example 1 produced above.
[0175] The physical properties of the electrodes produced in Example 1, Example 2, and Comparative Examples 1 to 3 are summarized in Table 1 below.
[0176] [Table 1]
[0177] According to Table 1 and FIG. 5, it was confirmed that the electrodes of Example 1 to Example 3, which have a compression rate of 15% or less, had good wrinkles in the uncoated area, while the electrodes of Comparative Example 1 to Comparative Example 3, which have a compression rate of more than 15%, had poor wrinkles in the uncoated area. In particular, referring to FIG. 5, it was confirmed that the electrode of Comparative Example 2 had a porosity of 35% or less before lamination, but had a high porosity ratio, so not only did wrinkles occur at the boundary between the uncoated area and the coated area, but wrinkles also occurred in the coated area. The electrode of Comparative Example 3 had a porosity of 30% or less after lamination and a porosity ratio of 140% or less, but had a porosity of 35% or more before lamination, and had a high compression rate and length expansion rate of more than 15% and more than 4%, respectively, so that the phenomenon of the electrode film being pressed during lamination was strongly observed, and as a result, it was confirmed that wrinkles in the lateral direction of the electrode and wrinkles at the boundary between the uncoated area and the coated area were particularly strong.
[0178] In addition, in the case of Example 3, in which the electrode film was obtained under high pressure in the calendar processing step during the production of the electrode film, it was confirmed that the wrinkle characteristics were significantly improved by decreasing the compression rate in the lamination step to 1% or less, thereby decreasing the length expansion rate and void ratio.
[0179] The present invention has been described above with reference to the embodiments and drawings. However, a person having ordinary knowledge in the field to which the present invention belongs can make various applications and modifications within the scope of the present invention based on the above content. [Explanation of symbols]
[0180] 100: Calendar process 110: Calendar roller 120: Mixed powder for electrodes 130: Electrode film 200: Lamination process 210: Laminating roller 220: Current collector 230: Electrode film 240: Electrode
Claims
1. (S10) mixing an electrode material including an electrode active material and a binder polymer to obtain a mixture; (S20) kneading the mixture at a high temperature and low shear rate to obtain a mixture mass; (S30) pulverizing the mixture mass under high shear to obtain a mixed powder for an electrode; (S40) calendaring the electrode powder mixture to obtain an electrode film; (S50) laminating the electrode film on at least one surface of a current collector to form an electrode active material layer; The electrode film has a compressibility of 15% or less, and the compressibility of the electrode film is defined by the following formula 1: [Formula 1] Compression ratio (%) = [(T B -T A ) / T B ]×100 In the above formula 1, T A is the thickness of the electrode film (electrode active material layer) after lamination, T B is the thickness of the electrode film before lamination.
2. The length expansion rate of the electrode film is 4% or less, and the length expansion rate is defined by the following formula 2: [Formula 2] Length expansion rate (%) = [(L A -L B ) / L B ]×100 In the formula 2, L A is the length of the electrode film (electrode active material layer) after lamination, L B The method for producing an electrode according to claim 1 , wherein x is the length of the electrode film before lamination.
3. The porosity ratio of the electrode film is 100% to 140%, and the porosity ratio of the electrode film is defined by the following formula 3: [Formula 3] Void ratio (%) = (P B / P A )×100 In the formula 3, P A is the porosity of the electrode film (electrode active material layer) after lamination, P B The method for producing an electrode according to claim 1 , wherein R is the porosity of the electrode film before lamination.
4. 2. The method for manufacturing an electrode according to claim 1, wherein the porosity of the electrode film before lamination in step (S50) is 35% or less, and the porosity of the electrode film after lamination is 30% or less.
5. The method for manufacturing an electrode according to claim 1, wherein the calendering in step (S40) is performed once or more than twice, and includes at least one calendering under a pressure of 100 kg / cm or more.
6. The method for producing an electrode according to claim 1, wherein the kneading in the step (S20) is carried out at a shear rate in the range of 10 / s to 500 / s for 1 minute to 30 minutes.
7. The method for producing an electrode according to claim 1, wherein the kneading in step (S20) is performed at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure.
8. The method for producing an electrode according to claim 1 , further comprising the step of forming a primer layer on at least one surface of the current collector before the lamination in the step (S50).
9. An electrode comprising: a current collector; and an electrode active material layer located on at least one surface of the current collector, the electrode active material layer comprising an electrode active material and a binder polymer, The binder polymer is fibrous to bind the electrode active material, the electrode comprises a grounded portion including the electrode active material layer and a current collector region facing the electrode active material layer, and an uncoated portion extending from both sides of the current collector region of the grounded portion and including a current collector region not facing the electrode active material layer, The porosity of the electrode active material layer is 30% or less, An electrode, wherein the surface of the uncoated portion is flat.
10. The electrode of claim 9 , further comprising a primer layer between the current collector and the electrode active material layer.
11. 11. An electrochemical element comprising: a positive electrode; a negative electrode; and a separation layer interposed between the positive electrode and the negative electrode, at least one of the positive electrode and the negative electrode being the electrode according to claim 9 or 10.
12. 12. The electrochemical device according to claim 11, wherein the separation layer is a separation membrane or a solid electrolyte membrane.
Citation Information
Patent Citations
Electrode for secondary battery
JP2007026984A
Electrode manufacturing method
JP2021125460A
Method for manufacturing battery electrode plate
WO2010035474A1